2022
DOI: 10.1183/23120541.00095-2022
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of occupational exposure to mineral fibres and recurrent chest infections in insulators

Abstract: Mineral fibres, which are types of commercially produced man-made vitreous fibres (MMVFs) with a woolly consistency, are industrially manufactured by passing air through molten glass, rock or slag, and are commonly known as glass, slag or rock wool. Although all these materials are grouped together as mineral fibres, there are differences in their composition and physical properties. Glass wool/fibreglass is made from borosilicate glass, which is composed of sand, soda ash dolomite, limestone, ulexite and anhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…All participants were screened at Synergy Respiratory Care Clinic, Sherwood Park, Alberta. Details of the study design, inclusion and exclusion criteria, and methodologies have been reported elsewhere ( 7 , 8 ). In brief, participants of at least 18 years of age, employed full-time as insulators, and of sound mental and cognitive ability at the time of screening were included in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were screened at Synergy Respiratory Care Clinic, Sherwood Park, Alberta. Details of the study design, inclusion and exclusion criteria, and methodologies have been reported elsewhere ( 7 , 8 ). In brief, participants of at least 18 years of age, employed full-time as insulators, and of sound mental and cognitive ability at the time of screening were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Several new man-made materials, often known as man-made vitreous fibers (MMVFs), aerogels, carbon fibers, mineral fibers, and refractory ceramic fibers (RCFs), have been introduced as potential insulating materials after many countries have imposed a ban on the use of asbestos. Most of these fibers also possess significant health hazards, particularly affecting the respiratory system that led to numerous adverse conditions such as chronic chest infection, carcinoma, adverse pleural conditions, and to some extent, obstructive and interstitial changes in the lungs (1)(2)(3)(4)(5)(6)(7)(8). However, despite the ban on asbestos use, workers, particularly construction workers and insulators, are often exposed to it, for example, during the demolition or renovation of old construction and insulations (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…All participants were screened at Synergy Respiratory Care Clinic, Sherwood Park, Alberta. Details of the study design, inclusion and exclusion criteria, and methodologies have been reported elsewhere [1,2]. In brief, the participants were administered a questionnaire containing items of demographic profile, personal and family history .…”
Section: In This Cross-sectional Study We Investigated 843 Unionized ...mentioning
confidence: 99%
“…Several new man-made materials, often known as man-made vitreous fibres (MMVFs), aerogels, carbon fibers, mineral fibers, and refractory ceramic fibers have been introduced as alternative insulating materials after many countries imposed a ban on the use of asbestos. Most of these fibres also possess significant health hazards, particularly affecting the respiratory system leading to numerous adverse conditions such as chronic chest infection, carcinoma, adverse pleural conditions, and to some extent, obstructive and interstitial changes in the lungs [1][2][3][4][5][6][7][8][9][10]. However, despite the ban on asbestos use, workers, particularly construction workers and insulators continue to be exposed to these materials, for example, during demolition, removal, or renovation of old constructions, insulation, etc.…”
Section: Introductionmentioning
confidence: 99%